Mathematical Modeling and Analysis of Eutrophication of Water Bodies Caused by Nutrients - Misra, A. K. K. (Nonlinear Analysis: Modelling and Control, 2007)
In this paper a non-linear mathematical model is proposed for a qualitative representation of ecosystem dynamics in a eutrophied water body. The model variables are the concentration of nutrients, densities of algal population, zooplankton population, detritus and the concentration of dissolved oxygen. The model consists of five coupled ordinary differential equations. By using the qualitative theory of differential equations the model steady-state dynamics are studied. Simulation analysis is also performed to see the effect of rate of input of nutrients on different variables participating in the proposed model.
Keywords: eutrophication; algae; zooplankton; detritus; dissolved oxygen